Constructing and imagining labour migration perspectives of control from five continents - Guild, Elspeth; Mantu, Sandra (Ashgate Pub., 2011)
Labour migration has been on the agenda of many countries around the globe at the same time as governments of both sending and receiving countries have been trying to develop regulatory mechanisms. This book opens the debate on the global politics of labour migration.